2005
DOI: 10.1097/01.qai.0000170034.90438.68
|View full text |Cite
|
Sign up to set email alerts
|

Early Monitoring of Ribavirin Plasma Concentrations May Predict Anemia and Early Virologic Response in HIV/Hepatitis C Virus-Coinfected Patients

Abstract: Ribavirin (RBV) in combination with pegylated interferon alpha (pegIFN) is currently the standard treatment of hepatitis C virus (HCV) infection. The development of anemia requires a reduction in RBV doses in a substantial proportion of patients, limiting their chances of treatment response. The primary goal of this study was to assess if early monitoring of RBV plasma levels could help to predict anemia as well as early HCV RNA response in HIV/HCV-coinfected individuals. The secondary goal was to evaluate if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
61
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 33 publications
12
61
2
1
Order By: Relevance
“…Otherwise, it has been demonstrated that anemia is related to the intra-erythrocytic and plasma concentrations of RBV (Caviglia et al, 2012;D'Avolio et al, 2012a;D'Avolio et al, 2013;D'Avolio et al, 2012c;De Franceschi et al, 2000;De Nicolò et al, 2013;Kubota et al, 2010;Loustaud-Ratti et al, 2008;Loustaud-Ratti et al, 2011;Morello et al, 2008;Rendon et al, 2005), moreover RBV plasma and intra-erythrocytic concentrations are correlated with the RBV doses taken by patients. Otherwise, RBV concentration is not only dependent on the administered dose, but also on body weight, absorption (nucleoside transporters and food effect) and excretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, it has been demonstrated that anemia is related to the intra-erythrocytic and plasma concentrations of RBV (Caviglia et al, 2012;D'Avolio et al, 2012a;D'Avolio et al, 2013;D'Avolio et al, 2012c;De Franceschi et al, 2000;De Nicolò et al, 2013;Kubota et al, 2010;Loustaud-Ratti et al, 2008;Loustaud-Ratti et al, 2011;Morello et al, 2008;Rendon et al, 2005), moreover RBV plasma and intra-erythrocytic concentrations are correlated with the RBV doses taken by patients. Otherwise, RBV concentration is not only dependent on the administered dose, but also on body weight, absorption (nucleoside transporters and food effect) and excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the only modifiable feature is RBV pharmacokinetic exposure, which shows a remarkable variability among HCV-infected patients (Tsubota et al, 2003). In fact, early assessment of RBV concentration is suggested by some studies (Caviglia et al, 2012;D'Avolio et al, 2012a;Loustaud-Ratti et al, 2008;Morello et al, 2008;Rendon et al, 2005) in order to adjust individual RBV dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to predict which patients will develop hemolytic anemia from ribavirin treatment. Prior studies have found an association between hemoglobin decline and increased ribavirin concentrations in plasma (15,16) and RBCs (17). Another study found that total intracellular ribavirin concentrations in RBCs, but not plasma levels, were significantly correlated with hemoglobin decline, which suggested that ribavirin levels in RBC would be a preferable parameter for assessing ribavirin-induced hemolytic anemia (18).…”
mentioning
confidence: 99%
“…The association between RBV C trough and relapse supports the essential role of RBV exposure in the clearance of HCV and highlights the idea that besides influencing the early decay of HCV clearance (18,19), it may influence as well the risk of HCV relapse independently of any effect on RVR, as recently shown in trials testing HCV protease inhibitors (9,10). This observation is important since monitoring of RBV C trough at week 4 might allow adaptation strategies to maximize the chances of cure with standard HCV therapy.…”
mentioning
confidence: 99%